2006
DOI: 10.1631/jzus.2006.b0837
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of expression of vascular endothelial growth factor and its receptors in pulmonary adenocarcinoma cell by TNP-470 in combination with gemcitabine

Abstract: Angiogenesis is required for solid tumor growth and facilitates tumor progression and metastasis. The inhibition effects of O-(chloroacetyl-carbamoyl) fumagillol (TNP-470), an angiogenesis inhibitor, and gemcitabine, a chemotherapeutic agent, on expression of growth factors were investigated using human pulmonary adenocarcinoma cell line, A549. The A549 cells were divided into four groups: control group, 10 −6 mg/ml gemcitabine treated group, 10 −4 mg/ml TNP-470 treated group and gemcitabine+TNP-470 treated gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Treatment of cells with heparinase to dissociate VEGF from heparin/heparan sulfate-binding sites revealed a reserve of VEGF in the hyperoxia-treated cells. As A549 cells are known to express both VEGFR1 and VEGFR2 protein, the results of the present study could reflect a shift in VEGF binding from receptors to heparin moieties [38]. Indeed hyperoxia has been shown to reduce VEGFR1 and VEGFR2 expression in the lungs of rats [39].…”
Section: Discussionmentioning
confidence: 54%
“…Treatment of cells with heparinase to dissociate VEGF from heparin/heparan sulfate-binding sites revealed a reserve of VEGF in the hyperoxia-treated cells. As A549 cells are known to express both VEGFR1 and VEGFR2 protein, the results of the present study could reflect a shift in VEGF binding from receptors to heparin moieties [38]. Indeed hyperoxia has been shown to reduce VEGFR1 and VEGFR2 expression in the lungs of rats [39].…”
Section: Discussionmentioning
confidence: 54%
“…Studies on xenografts of human gastric cancer cells, pulmonary adenocarcinoma cells and prostate cancer cells showed that the combination therapy of TNP-470 and cytotoxic drug can improve the clinical efficacy, reduce drug dosage and toxicity and adverse drug reactions [23][24][25][26] . Up to present, few reports on TNP-470 in combination with other treatment methods in the treatment of human glioma cell xenografts are available.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical evidence indicated that combining antiangiogenic agents with a conventional chemotherapeutic agent therapy results in additive or even synergistic antitumoral effect (12,29,30). Several studies have shown that the combination of newly developed anti-angiogenic agents (DC101, SU5416 and TNP-470) and GEM inhibited the tumor growth and angiogenesis synergistically in pancreatic cancer experimental models (31). Although several anti-angiogenic agents have already been employed in the clinical practice, these newly developed agents frequently induce severe side effects such as perforation of the gastrointestinal tract and hand-foot syndrome (32,33).…”
Section: Discussionmentioning
confidence: 99%